Multimodality as universality: Designing inclusive accessibility to graphical information - Doore, Stacy A.; Dimmel, Justin; Kaplan, Toni M.; Guenther, Benjamin A.; Giudice, Nicholas A. (Frontiers in Education, 2023)
Graphical representations are ubiquitous in the learning and teaching of science, technology, engineering, and mathematics (STEM). However, these materials are often not accessible to the over 547,000 students in the U.S. with blindness and significant visual impairment, creating barriers to pursuing STEM educational and career pathways. Furthermore, even when such materials are made available to visually impaired students, access is likely through literalized modes (e.g., braille, verbal description), which is problematic as these approaches (1) do not directly convey spatial information and (2) are different from the graphic-based materials used by students without visual impairment. The purpose of this study was to design and evaluate a universally accessible system for communicating graphical representations in STEM classes. By combining a multisensory vibro-audio interface and an app running on consumer mobile hardware, the system is meant to work equally well for all students, irrespective of their visual status. We report the design of the experimental system and the results of an experiment where we compared learning performance with the system to traditional (visual or tactile) diagrams for sighted participants (n=20) and visually impaired participants (n=9) respectively. While the experimental multimodal diagrammic system (MDS) did result in significant learning gains for both groups of participants, the results also revealed no statistically significant differences in the capacity for learning from graphical information across both comparison groups. Likewise, there were no statistically significant differences in the capacity for learning from graphical information between the stimuli presented through the experimental system and the traditional (visual or tactile) diagram control conditions, across either participant group. These findings suggest that both groups were able to learn graphical information from the experimental system as well as traditional diagram presentation materials. This learning modality was supported without the need for conversion of the diagrams to make them accessible for participants who required tactile materials. The system also provided additional multisensory information for sighted participants to interpret and answer questions about the diagrams. Findings are interpreted in terms of new universal design principles for producing multisensory graphical representations that would be accessible to all learners.